Examining the implementation of Teacher–Child Interaction Training‐Universal in public schools. Issue 11 (6th June 2022) - Santiago, Catherine DeCarlo; Bustos, Yvita; Sosa, Susana S.; Jolie, Sarah A.; Flores Toussaint, Roxanna; Gebhardt, Sarah; Stern, David; Budd, Karen S.
Abstract: The Teacher–Child Interaction Training‐Universal (TCIT‐U) is a professional development program for teachers that promotes positive relational interactions and strengthens classroom management. This study examines the implementation of TCIT‐U in a public school district to guide future implementation and sustainability. This study uses qualitative methods to examine the implementation of TCIT‐U across preschool through second‐grade classrooms in a suburban public school district in Illinois, United States. Eight teachers and five coaches participated in focus groups, while three administrators completed interviews. Qualitative data from focus groups and interviews are supplemented by quantitative data on satisfaction, teacher sense of efficacy, teacher observations, and school records. Results demonstrated high levels of acceptability, good feasibility, high satisfaction, and several notable improvements across teachers and students, such as improved teachers' confidence and self‐efficacy in managing classrooms. Nevertheless, there were implementation challenges, including timing, competing demands, and district priorities. The results from this study offer guidance for future implementation of TCIT‐U as an acceptable, feasible, and universal intervention. Practitioner points: Teacher–Child Interaction Training‐Universal demonstrated high levels of acceptability and feasibility. Facilitators of implementation included high‐quality training and coaching, notable improvements for students and teachers, adaptability, and compatibility with school priorities. Barriers to implementation included timing of adoption, competing demands, variable support from administrators, and financial resources.